2001
DOI: 10.1111/j.1572-0241.2001.03681.x
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole Treatment of Patients With Chronic Idiopathic Laryngitis: A Placebo-Controlled Trial

Abstract: Empirical treatment with lansoprazole is efficacious in relieving symptoms of laryngitis compared to placebo. Such treatment can be considered as a first-line option in managing patients with idiopathic chronic laryngitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
2
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(67 citation statements)
references
References 18 publications
2
58
2
5
Order By: Relevance
“…In keeping with a putative role for GERD in eliciting the symptoms, we obtained a marked reduction of the predominant ENT symptoms in the majority of patients after, on average, 4 weeks of PPI therapy with omeprazole, 20 mg b.i.d. The response rates to PPI therapy in the present study are high compared to those in a number of other publications (32,33), but we suspect that this mainly reflects patient selection and is in line with our own previous observations (22)(23)(24)(25). We recruited consecutive patients from the ENT clinic for a full reflux investigation, while we suspect that previous studies dealt with selected ENT patients referred to the gastroenterologist because of particularly difficult and refractory symptoms.…”
Section: Discussionsupporting
confidence: 83%
“…In keeping with a putative role for GERD in eliciting the symptoms, we obtained a marked reduction of the predominant ENT symptoms in the majority of patients after, on average, 4 weeks of PPI therapy with omeprazole, 20 mg b.i.d. The response rates to PPI therapy in the present study are high compared to those in a number of other publications (32,33), but we suspect that this mainly reflects patient selection and is in line with our own previous observations (22)(23)(24)(25). We recruited consecutive patients from the ENT clinic for a full reflux investigation, while we suspect that previous studies dealt with selected ENT patients referred to the gastroenterologist because of particularly difficult and refractory symptoms.…”
Section: Discussionsupporting
confidence: 83%
“…To use higher than approved doses of PPI is suggested in some situations [16]. One of the times that this is of particular benefit is during a diagnostic trial for supraesophageal symptoms of GERD [17]. Several studies have suggested that the empiric therapy has to be aggressive, with a period of treatment of at least 2-3 months [1,18,19].…”
Section: Treatmentmentioning
confidence: 99%
“…All studies have failed to show a significant effect of PPIs over placebo [3,4], except one [5] that included a very low number of patients and had a 0% placebo response. Up to 50% of the patients with GERD may require continuous medical therapy to prevent relapse [6].…”
mentioning
confidence: 96%